Objectives of the ESG bonds issues - Frydrych, Sylwia (Ekonomia i Prawo. Economics and Law, 2023)
Motivation: In the face of a growing interest in social, environmental, and sustainable economic development in recent years, attention should be paid to debt instruments with an ESG label. Proceeds from the issue of these instruments are intended for purposes related to the financing of projects contributing to meeting the ESG criteria. Aim: The aim of the article is to analyse the objectives of the ESG bond issues. The study is an attempt to answer the question which industries issue ESG bonds, contributing to the fulfilment of ESG criteria, and for what purposes the funds from the issue are allocated. Results: Database collected from the Refinitiv Eikon for the period between 2012 and 2021 allows also to conclude that there is weak positive relationship between sectors and ESG bond issuance objectives. Whereas there is strong positive relationship between ESG bond issue objectives such as Clean Transport, Energy Efficiency, Eligible Green Projects, Green Construction Buildings and Alternative Energy. On the other hand, an inverse weak relationship has been observed between issue’s targets such as Climate Change Adaptation and Renewable Energy Project as well as Climate Change Adaptation and Alternative Energy.